A utilização do eletroencefalograma como biomarcador na Doença de Parkinson - Costa, Thaísa Dias de Carvalho (2021)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms. This disease is increasingly prevalent at older ages, therefore, the study of sensitive biomarkers favors the clinical and therapeutic management of PD. For this, the electroencephalogram (EEG) can be used to assess the electrical activity of the brain, and an analysis of the multichannel EEG can provide different information from the electrophysiology, probably to be altered in PD. The general objective of the present study was to investigate whether the EEG can be used as a marker in PD. Two studies were developed, the first consists of a scoping review of the literature to identify the nature and extent of evidence on the effects of non-invasive brain stimulation (NIBS) techniques on cortical activity measured by EEG in patients with PD, and the second is an observational study with the objective to identify possible biomarkers through the analysis of EEG microstates and their clinical correlates in PD. The scoping review (study 1) indicated that NIBS can promote EEG effects in individuals with PD, accompanied by clinical improvement in some studies. The observational study (study 2) was developed with a PD group with 10 individuals and a control group with 10 healthy individuals, and significant changes were observed in microstate C, in addition to correlations between microstates B, C and D with non-motor aspects of PD. Therefore, the results of the present dissertation suggest that the monitoring of EEG data in parallel with the treatment and progression of PD can be used to assist the clinical management of the disease, despite the limitations of the articles developed, such as the scarcity and heterogeneity of studies in the first article and small sample in the second article. It is hoped that these findings are encouraging for further investigations.